DNA polymerase gamma (Polγ) deficiency triggers a selective mTORC2 prosurvival autophagy response via mitochondria-mediated ROS signaling. Issue 48 (29th November 2018) - Dhar, Sanjit; Bakthavatchalu, Vasudevan; Dhar, Bithika; Chen, Jing; Tadahide, Izumi; Zhu, Haining; Gao, Tianyan; St. Clair, Daret
Abstract Autophagy is a highly regulated evolutionarily conserved metabolic process induced by stress and energy deprivation. Here, we show that DNA polymerase gamma (Polγ) deficiency activates a selective prosurvival autophagic response via mitochondria-mediated reactive oxygen species (ROS) signaling and the mammalian target of rapamycin complex 2 (mTORC2) activities. In keratinocytes, Polγ deficiency causes metabolic adaptation that triggers cytosolic sensing of energy demand for survival. Knockdown of Polγ causes mitochondrial stress, decreases mitochondrial energy production, increases glycolysis, increases the expression of autophagy-associated genes, and enhances AKT phosphorylation and cell proliferation. Deficiency of Polγ preferentially activates mTORC2 formation to increase autophagy and cell proliferation, and knocking down Rictor abrogates these responses. Overexpression of Rictor, but not Raptor, reactivates autophagy in Polγ-deficient cells. Importantly, inhibition of ROS by a mitochondria-selective ROS scavenger abolishes autophagy and cell proliferation. These results identify Rictor as a critical link between mitochondrial stress, ROS, and autophagy. They represent a major shift in our understanding of the prosurvival role of the mTOR complexes and highlight mitochondria-mediated ROS as a prosurvival autophagy regulator during cancer development.